PENETAPAN STATUS KAMPUNG WISATA PADA KELURAHAN TEBING TINGGI OKURA KOTA PEKANBARU - Yanti, Risna; Fitria Hasibuan, Ika; Handayani, Elwira; Abdisalam, Fazli; Febdarina, Sri; Lestari, Lisa (JURNAL MEKAR, 2025)
This research examines the Determination of Tourism Village Status in Tebing Tinggi Okura Village, Pekanbaru City. This study aims to determine the status of Tebing Tinggi Okura Village based on the ASEAN Community-Based Tourism Standard (ASEAN CBT) tourism village assessment criteria. The scope of this study covers eight criteria and sub-criteria for tourism village assessment. The location is Tebing Tinggi Okura Village, Rumbai Timur District, Pekanbaru City.This research was conducted from October 2024 to April 2025. The data used were qualitative, while the data sources were primary and secondary. Data collection techniques included field research (in-depth interviews, observations, and questionnaires) using the Delphi method, triangulation techniques, and literature review. The data analysis technique used was descriptive analysis. Based on the research results, which refer to the eight criteria for tourism village assessment according to the ASEAN Community-Based Tourism (CBT) Standard, it can be concluded that Okura Tourism Village is still in the early stages of developing its community-based tourism potential. Administratively, the village has a tourism institution in the form of a Tourism Awareness Group (Pokdarwis). In terms of environmental quality, the village is considered quite good, but there is no collectively directed management system or program. Community participation in tourism is also low. Support services such as tour guides, tourist information, reservation systems, and itinerary planning are not yet available. Food and beverages are still basic and served only during annual events, while the existing homestays are not yet professionally managed and only operate seasonally. Based on these indicators, Okura Tourism Village can currently be classified as a pioneering tourism village.